Investigation of Aquifer Model to Potential of Ground Movement at Brau Village, Kota Wisata Batu, Jawa Timur, indonesia - Maha Agung, Putera Agung; Gautama, Gregorius Aryoko; Istiatun; Amir, Mardiana; Adinegara, Aldo Wirastana; Eko Wiyono; Wacono, Sidiq (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Soft soils at Brau Village area, Kota Wisata Batu (KWB) usually form in alluvial highlands due to weathering of sedimentary rocks. An upper and lower aquifer of sandy layer exist between soft soil. Groundwater pools into aquifer layers and infiltration from surface water into the soft soil layers (clayey and/ or silty) generated a ground movement potential. Study will elaborate the behavior of layers of clayey and/ or silty separated by 2 (two) aquifer layers in detail causing some damages to infrastructure. Wall and/ or floor cracks at school buildings and collapse and/ or differential settlement in road pavement  are a failure of soil layers due to high pore water pressure coming from direction of aquifer zone especially during rainy season. Pore water pressures were determined by rate of settlement prediction from consolidation laboratory analyzed by Ying et al (2015) and actual measurement using electromagnetic data. Research results found that gradually increment of pore water pressure would exceed a total stress in reducing an effective stress drastically and created a location of initial ground movement at the toe of slope around infrastructure area. High pore water pressure due to the increment of water volume at aquifer layer can push down soil layers with safety factor (SF) < 1.0. At the same time, ground movement would generate cracks > 10 cm width at wall and floor of school building structure; and collapse or differential settlement occurred in road construction > 18 cm depth due to bonding agent separated between soil particles.